Health service access, use, and insurance coverage among American Indians/Alaska Natives and Whites: What role does the Indian Health Service play? - Zuckerman, Stephen; Haley, Jennifer; Roubideaux, Yvette; Lillie-Blanton, Marsha (Health Sciences Research Commons, 2004)
Although the health status of American Indians and Alaska Natives (AIANs) improved after the establishment of the Indian Health Service (IHS) in 1955, significant health disparities persist. The federal government attempts to meet its commitment to provide health care for AIANs through a system of hospitals and clinics on or near reservations, managed by the IHS and, more recently, by Indian tribes. IHS facilities provide primary care services free of charge, and limited free specialty services are available through contracts with private providers. However, services available through the IHS vary widely across tribes, and IHS hospitals are not available in all service areas. Many communities have small clinics and must contract out for all specialty care, x-ray services, and other diagnostic tests and routine preventive care such as mammograms. Services can vary and may be limited by significant shortfalls in funding.